Munroa argentina, a grass of the South American transtion zone, survived the Andean uplift, aridification and glaciations of the quaternary - Amarilla, Leandro; Anton, Ana Maria Ramona; Chiapella, Jorge Oscar; Manifesto, Maria Marcela; Angulo, Diego Francisco; Sosa, Victoria (2017)
The South American Transition Zone (SATZ) is a biogeographic area in which not only orogeny (Andes uplift) and climate events (aridification) since the mid-Miocene, but also Quaternary glaciation cycles had an important impact on the evolutionary history of the local flora. To study this effect, we selected Munroa argentina, an annual grass distributed in the biogeographic provinces of Puna, Prepuna and Monte. We collected 152 individuals from 20 localities throughout the species’ range, ran genetic and demographic analyses, and applied ecological niche modeling. Phylogenetic and population genetic analyses based on cpDNA and AFLP data identified three phylogroups that correspond to the previously identified subregions within the SATZ. Molecular dating suggests that M. argentina has inhabited the SATZ since approximately 3.4 (4.2–1.2) Ma and paleomodels predict suitable climate in these areas during the Interglacial period and the Last Glacial Maximum. We conclude that the current distribution of M. argentina resulted from the fragmentation of its once continuous range and that climate oscillations promoted ecological differences that favored isolation by creating habitat discontinuity.